The Life of Benjamin Franklin, Volume 1 : Journalist, 176-173 - Lemay, J. A. Leo (Joseph A. Leo), 1935-2008 (Book collections on Project MUSE., 2006)
Representing a lifetime of research by the dean of Franklin scholars, this seven-volume biography will give enthusiasts and scholars an important resource for understanding Benjamin Franklin's character and place in American history. This first volume chronicles the early years of Franklin, from his birth to his marriage in 1730.